Impact of a comprehensive healthy lifestyle on pre-diabetes risk and glycaemic control: insights from NHANES 2005–2018 - Hongmei Xu; Wenyan Xu; Yingying Li; Jiayin Qin; Dandan Sun; Di Bao; Chun Mu; Qiuling Xing (BMJ Nutrition, Prevention & Health)
Objective To evaluate the association between a comprehensive multidimensional healthy lifestyle and the risk of pre-diabetes and glycaemic control markers, specifically glycated haemoglobin (HbA1c) and fasting plasma glucose (FPG), and to conduct subgroup analyses to examine these associations across different populations.Methods A cross-sectional analysis of 9567 adults aged 20 and older was conducted using data from the National Health and Nutrition Examination Survey from 2005 to 2018 participants. A lifestyle score was created based on eight modifiable factors: diet, physical activity, smoking, alcohol consumption, sleep duration, waist circumference, depressive symptoms and marital status. Weighted logistic regression estimated ORs for pre-diabetes, and linear regression assessed associations with HbA1c and FPG.Results A higher healthy lifestyle score was associated with a significantly lower risk of pre-diabetes and improved glycaemic markers. Compared with participants with 0–2 healthy lifestyle factors, those with 7–8 factors exhibited a 53% lower risk of pre-diabetes (OR: 0.47, 95% CI: 0.31 to 0.69; p<0.001, P for trend <0.001). The results showed significant reductions in HbA1c by 0.08 units (95% CI: −0.16 to −0.01) and in FPG by 2.74 mg/dL (95% CI: −4.47 to −1.01). Stratified analyses showed stronger associations in women, individuals without a family history of diabetes, and those aged 40–59. Sensitivity analyses confirmed the robustness of these findings.Conclusions The study results highlight the value of a multidimensional, modifiable healthy lifestyle in reducing pre-diabetes risk and improving glycaemic control. These results support integrated lifestyle interventions in population-level pre-diabetes prevention strategies.